Computed Tomography Perfusion Following Transarterial Chemoembolization of Hepatocellular Carcinoma: A Feasibility Study in the Early Period. Issue 5 (September 2017) - Wimmer, Thomas; Steiner, Juergen; Talakic, Emina; Stauber, Rudolf; Quehenberger, Franz; Portugaller, Rupert Horst; Schoellnast, Helmut
Abstract : Objectives: The aim of this study was to assess the feasibility of computed tomography (CT) perfusion in early follow-up after transarterial chemoembolization (TACE) of hepatocellular carcinoma (HCC). Methods: Fifteen patients with a total of 16 HCC who were referred to our institution for TACE were included in the study. Computed tomography perfusion was performed within 1 to 3 days before and 4 to 7 days after TACE. Multiphase contrast-enhanced CT was performed 35 (SD, 20) days after TACE. Hepatic arterial blood flow and portal venous blood flow, as well as the perfusion index (PI), were calculated for each HCC using the dual input maximum slope method. Visual grading of the PI and visual grading of the amount of deposition of embolic material within the HCC were performed using a 6-step scale. Differences in perfusion before and after TACE and correlation of perfusion before TACE with the amount of embolization material depositions 1 week and 1 month after TACE were tested. Results: No statistically significant correlation was found between pre-TACE perfusion parameters and the amount of embolization material deposition in the post-TACE studies. There was no statistically significant difference between pre- and post-TACE arterial blood flow and portal venous blood flow, whereas PI was significantly lower after TACE. Congruently, visual grading of PI was statistically significantly lower after TACE. There was no statistically significant difference in quantitative pre-TACE and post-TACE PI between tumors, which showed hypervascularization in the multiphase follow-up CT and tumors that did not show hypervascularization. However, tumors that showed hypervascularization in the multiphase follow-up CT had significantly higher visual grading of PI after TACE than tumors that did not show hypervascularization. Conclusions: Our findings indicate that visual interpretation of the PI of HCC derived from dual-input maximum slope CT perfusion may be an early predictor of response to TACE.